Modified force/displacement-based procedure for performance-based seismic design of regular RC frames - ElKassas, Soha Hassan Nashaat (AUC Knowledge Fountain, 2019)
Performance-based seismic design has been the thrust of international research on earthquake engineering for the past 20 years. The major decisive factor for the success of its most recent framework is the development of efficient â€œpreliminary designâ€ methodologies that follow common design formats in order to maintain the process at an affordable level of complexity for practitioners. Using the traditional force-based seismic design method for this purpose, though simple and easy, will be inefficient because it designs structures to only one performance objective (which is life safety), and any other performance objective would be part of the drift check that follows the design, which will result in a highly iterative process. Therefore, in order to use the standard seismic design method in the context of the performance-based framework, there is a need for its adjustment to match the multi-level performance concept, by incorporating the performance measures at the beginning. The potential of a hybrid force/displacement design format in this respect has been well recognized and developed over a decade for steel structures. The method is characterized by the establishment of a direct analytical link between the performance requirements and the reduction of elastic forces to the design force level, in a format that mixes the advantages of both force-based and displacement-based methods. Using the same analytical architecture, this thesis, titled â€œModified Force/Displacement-based Procedure for Performance-based Seismic Design of Regular RC Frames,â€ proposes a â€œtoolâ€ for preliminary design of RC framed structures that can be suitable for the design office environment. The methodology uses displacement demand as input parameter, which more rationally represent actual earthquake response and eliminates the iterative steps required to satisfy the acceptable performance limits in the traditional code design procedure. The research serves to develop the displacement estimate relations for RC structures for use at the beginning of design, which lie at the heart of this design method. For development of these displacement prediction relations, prototype structures with various geometrical characteristics are selected for study. A rigorous modelling approach and validated analytical tool are utilized to perform nonlinear time-history analysis as the closest approximation of actual earthquake loading. Incremental dynamic analysis is performed, employing a diverse range of synthetically developed ground motion records, in order to identify the ground motion intensity at which three preselected damage levels are reached, as defined by the inter-story drift ratio (the chosen damage metric). Time-history analysis is conducted at those determined loading levels and the displacement response values are analyzed. Adopting nonlinear regression, equations are developed for estimating the roof displacement as a factor of the performance target (in terms of the inter-story drift ratio) and some structural attributes such as the number of floors and bays. This estimate can be used together with the roof yield displacement to derive a performance-dependent force-reduction factor, and design can then proceed in the conventional way. A design case study helps to prove the efficiency and higher reliability of the proposed modification in achieving targeted performance and thus its suitability for application in performance-based design, provided elimination of its limitations and broadening its scope of application.